2016
DOI: 10.1007/jhep09(2016)124
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational tension, spacetime pressure and black hole volume

Abstract: Abstract:We study the first law of black hole thermodynamics in the presence of surrounding gravitational fields and argue that variations of these fields are naturally incorporated in the first law by defining gravitational tension or gravitational binding energy. We demonstrate that this notion can also be applied in Anti-de Sitter spacetime, in which the surrounding gravitational field is sourced by a cosmological fluid, therefore showing that spacetime volume and gravitational tension encode the same physi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…In addition, the topology of all horizons in D = 5 encountered in this work is either S 3 or S 1 × S 2 , thus agreeing with the extremal near-horizon geometry classification of [43,44] and the uniqueness theorems of [45,46]. It would be interesting to obtain extremal versions of the black holes found in [20,36,47] in (Anti)-de Sitter spacetime and to check whether they also agree with [42,48].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, the topology of all horizons in D = 5 encountered in this work is either S 3 or S 1 × S 2 , thus agreeing with the extremal near-horizon geometry classification of [43,44] and the uniqueness theorems of [45,46]. It would be interesting to obtain extremal versions of the black holes found in [20,36,47] in (Anti)-de Sitter spacetime and to check whether they also agree with [42,48].…”
Section: Discussionsupporting
confidence: 70%
“…Amusingly, the result is the same as if the black hole were a ball of radius r + in Euclidean space. A recent contrasting viewpoint [95] is that thermodynamic volume should be replaced with a more general notion of gravitational tension that describes the extra energy associated with the presence of gravitational fields surrounding a black hole. Gravitational tension vanishes in the flat-space limit and is proportional r 3 + /l 3 for a Schwarzschild-AdS black hole.…”
Section: Thermodynamic Volumementioning
confidence: 99%
“…However a class of black holes has recently been found that violates this conjecture [45,46], necessitating further investigation of the role and meaning of the volume [47]. The relationship of V to other proposed notions of volume [48,49] is an ongoing subject of investigation.…”
Section: Introductionmentioning
confidence: 99%